2014
DOI: 10.1093/nar/gku771
|View full text |Cite
|
Sign up to set email alerts
|

Initiator protein dimerization plays a key role in replication control of Vibrio cholerae chromosome 2

Abstract: RctB, the initiator of replication of Vibrio cholerae chromosome 2 (chr2), binds to the origin of replication to specific 12-mer sites both as a monomer and a dimer. Binding to 12-mers is essential for initiation. The monomers also bind to a second kind of site, 39-mers, which inhibits initiation. Mutations in rctB that reduce dimer binding increase monomer binding to 12-mers but decrease monomer binding to 39-mers. The mechanism of this paradoxical binding behavior has been unclear. Using deletion and alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 51 publications
(95 reference statements)
2
30
0
Order By: Relevance
“…Binding was assessed for WT RctB (659 amino acids) and an N-terminal fragment consisting of amino acids 1 to 500 (RctB ΔC159). Previous work revealed that RctB ΔC159 binds to a 12-mer and a 39-mer with different affinities than WT ( 14 , 21 , 23 ), but it is not known if this RctB fragment binds to an 11-mer in a different manner than WT; this information might help explain why RctB ΔC159 is not subject to Inc-mediated negative regulation ( 14 , 21 , 23 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Binding was assessed for WT RctB (659 amino acids) and an N-terminal fragment consisting of amino acids 1 to 500 (RctB ΔC159). Previous work revealed that RctB ΔC159 binds to a 12-mer and a 39-mer with different affinities than WT ( 14 , 21 , 23 ), but it is not known if this RctB fragment binds to an 11-mer in a different manner than WT; this information might help explain why RctB ΔC159 is not subject to Inc-mediated negative regulation ( 14 , 21 , 23 ).…”
Section: Resultsmentioning
confidence: 98%
“…The mutant’s lack of inhibition by inc appears to reflect the higher affinity of ΔC159 mutant RctB than wild-type (WT) RctB for a 12-mer and its lack of binding to the 39-mer motifs found in oriCII ( 14 , 21 ). In addition, truncated forms of RctB have a lower capacity to dimerize than the full-length protein, and Chattoraj and colleagues have proposed that monomeric and dimeric forms of RctB promote and inhibit initiation at oriCII , respectively ( 23 ). The effects of the truncations are incompletely understood; nonetheless, their behavior has provided some insight into how RctB-mediated initiation at oriCII may be regulated ( 14 , 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Initiation from oriC2 requires RctB, which recognizes 11mer and 12mer iterons, and also a 39mer and a truncated form of the 39mer named the 29mer. The 39mer in the inc2 region and the 29mer bound by the monomeric form of RctB together with the DnaA box bound by V. cholerae DnaA regulate the frequency of initiation from oriC2 [37]. Adapted from Refs.…”
Section: Figmentioning
confidence: 99%
“…1). oriC2 contains an array of tandem repeats named the 11mer and 12mer that are bound by monomers and dimers of RctB [37,38]. Another DNA motif named the 39mer is specifically bound by monomeric RctB.…”
mentioning
confidence: 99%
“…RctB binds and hydrolyzes ATP but unlike DnaA, the ATP-bound form of RctB is inactive [14]. It binds to DNA as monomer or as a dimer [15,16]. Finally, RctB is most probably remodeled by chaperones DnaJ and DnaK similar to iteron-carrying plasmid's Rep initiators [15,17].…”
Section: Replication Initiation Of V Cholerae Chr1 and Chr2mentioning
confidence: 99%